The image and the brazen serpent: division, mediation and the translatability of cultures - de Villiers-Human, Suzanne (Acta Academica: Critical views on society, culture and politics, 2010)
This article confronts possible effects of the crisis of intercultural communication by investigating the transforming power of images to reorient or transfigure accepted cultural meanings. With current image theorists such as W J T Mitchell and Hans Belting it emphasises that the image’s power to self-create or to possess a life, presence or soul of its own – that aspect of the image that makes it seem animated and able to trap or immerse – is not merely a relic of ritual, cultic or idolatrous comprehensions, but may rather be one of the constant features in ontologies of the image.